SANSEVIERIA HYACINTHOIDES (L.) DRUCE: A REVIEW OF ITS BOTANY, MEDICINAL USES, PHYTOCHEMISTRY, AND BIOLOGICAL ACTIVITIES: ETHNOPHARMACOLOGY OF SANSEVIERIA HYACINTHOIDES - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Sansevieria hyacinthoides is a succulent perennial herb widely used as herbal medicine. This study is aimed at providing a critical review of the botany, biological activities, phytochemistry, and medicinal uses of S. hyacinthoides. Documented information on the botany, biological activities, medicinal uses, and phytochemistry of S. hyacinthoides was collected from several online sources which included BMC, Scopus, SciFinder, Google Scholar, Science Direct, Elsevier, PubMed and Web of Science. Additional information on the botany, biological activities, phytochemistry, and medicinal uses of S. hyacinthoides was gathered from pre-electronic sources such as book chapters, books, journal articles, and scientific publications obtained from the university library. This study showed that the leaf sap, leaves, rhizomes, roots, and whole plant parts of S. hyacinthoides are used as ethnoveterinary medicine, magical purposes, to dilate birth canal and as herbal medicine for fever, respiratory problems, intestinal parasites, worms, rheumatism, swellings, skin infections, sexually transmitted infections, hemorrhoids, toothache, diarrhea, stomach problems, insect and snake bites, earache, and infections. Phytochemical analyses revealed that the leaves, rhizomes, and roots are characterized by alkaloids, flavonoids, and steroids. Pharmacological research revealed that S. hyacinthoides crude extracts have anthelmintic, antibacterial, antifungal, and antioxidant activities. Future ethnopharmacological research should focus on carrying out detailed phytochemical, pharmacological, and toxicological studies.